Analisis Risiko terhadap Keselamatan dan Kesehatan Kerja dalam Proses Penggantian Katalis di Butane Treater di PT. X - Selamat, Selamat; Carlo, Nafryzal; Utama, Lusi (Universitas Batanghari Jambi, 2025)
Occupational health and safety (OHS) issues in the oil and gas industry are critical factors that influence worker safety and the operational continuity of companies. The oil and gas industry is known for its high-risk environment, which involves hazardous chemicals, high pressures, extreme temperatures, and the potential for accidents that can harm the environment. One of the high-risk activities in this industry is the catalyst replacement process in the butane treater, which is crucial for removing impurities from butane during gas processing. This process carries significant hazards, such as exposure to hazardous chemicals, fire, and explosion. This study aims to identify and analyze the OHS risks associated with the catalyst replacement process in the butane treater and to develop mitigation recommendations that can be implemented to minimize hazards and improve worker safety.The method used in this study is the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method, a systematic approach for identifying hazards, assessing risks, and determining appropriate control measures. This method allows for comprehensive hazard identification and risk mapping based on the probability and impact levels, enabling the proposal of effective mitigation actions. The study analyzes potential hazards that may arise during the catalyst replacement process and the mitigation procedures to reduce these risks.The results of the study show that the catalyst replacement process in the butane treater involves several key risks, such as exposure to hazardous gases, fire, explosion, and risks associated with improper work procedures. Proposed mitigations include enhancing standard operating procedures, safety training, the use of personal protective equipment (PPE), and the implementation of technical controls such as ventilation systems and equipment safety measures. By applying these recommendations, it is expected that the risk of accidents can be minimized, and worker safety can be better maintained.Top of Form